Activity of acute pancreatitis is modified by secreted protein acidic and rich in cysteine ablation. Issue 6 (14th June 2022) - Ammer‐Herrmenau, Christoph; Wolf, Laurin; Nasrin, Syeda S.; Ramu, Iswarya; Roggiolani, Roberta; Goetze, Robert G.; Buchholz, Soeren M.; Sendler, Mathias; Ellenrieder, Volker; Neesse, Albrecht
Abstract: Background: Acute pancreatitis (AP) is a frequent cause for hospitalization. However, molecular determinants that modulate severity of experimental pancreatitis are only partially understood. Objective: To investigate the role of secreted protein acidic and rich in cysteine (SPARC) during cerulein‐induced AP in mice. Methods: AP was induced by repeated cerulein injections in SPARC knock‐out mice (SPARC −/− ) and control littermates (SPARC +/+ ). Secreted protein acidic and rich in cysteine expression and severity of AP were determined by histopathological scoring, immunohistochemistry, and biochemical assays. For functional analysis, primary murine acinar cell cultures with subsequent amylase release assays were employed. Proteome profiler assay and ELISA were conducted from pancreatic tissue lysates, and co‐immunofluorescence was performed. Results: Upon cerulein induction, SPARC expression was robustly induced in pancreatic stellate cells (PSCs) but not in acinar cells. Genetic SPARC ablation resulted in attenuated severity of AP with significantly reduced levels of pancreatic necrosis, apoptosis, immune cell infiltration, and reduced fibrosis upon chronic stimulation. However, the release of amylase upon cerulein stimulation in primary acinar cell culture from SPARC +/+ and SPARC −/− was indistinguishable. Notably, immune cell derived C‐C Motif Chemokine Ligand 2 (CCL2) was highly elevated in SPARC +/+ pancreatic tissue potentially linking PSC derived SPARC with CCL2 induction in AP. Conclusion: SPARC mediates the severity of AP. The potential link between SPARC and the CCL2 axis could open new avenues for tailored therapeutic interventions in AP patients and warrants further investigations.